2002
DOI: 10.1002/app.10193
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and crosslinking of polyamide‐1010 under elevated pressure

Abstract: ABSTRACT:The structure and thermal properties of polyamide-1010 (PA1010), treated at 250°C for 30 min under pressures of 0.7-2.5 GPa, were studied with wide-angle X-ray diffraction (WAXD), infrared (IR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Crystals were formed when the pressures were less than 1.0 GPa or greater than 1.2 GPa. With increasing pressure, the intensity of the diffraction peak at approximately 24°was enhanced, whereas the peak at approximately 20°was depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…[3][4][5] Due to good mechanical properties and semicrystalline structure, the investigation of dielectric and electrical behaviors of nylon 1010 is important both from the fundamental and technological points of view. 1,2 Moreover, like other nylons, nylon 1010 is a typical semicrystalline polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Due to good mechanical properties and semicrystalline structure, the investigation of dielectric and electrical behaviors of nylon 1010 is important both from the fundamental and technological points of view. 1,2 Moreover, like other nylons, nylon 1010 is a typical semicrystalline polymer.…”
Section: Introductionmentioning
confidence: 99%
“…by cross-linking as reported by Yang et al [36,37] for nylon-1010 after treatment at 523 K in the 1.0 to 1.2 GPa range. Since the line width of an NMR resonance reflects dynamical processes, such as the exchange and reorientation speed of molecular movements, it can be used to detect cross-linking in polymers [38,39].…”
Section: Polymorphism and Cross-linking Properties By Solid State Nmrmentioning
confidence: 99%
“…In general, folded‐chain crystals are tough and ductile and tend to produce low modulus and high elongation, whereas extended‐chain crystals are brittle and tend to have higher modulus. After Wunderlich and Arakawa2 reported that polyethylene extended‐chain crystals with a thickness of up to 3 µm could be formed under high pressure, many researchers performed investigations on the high pressure crystallization behaviors of some polymers and obtained their extended‐chain crystals 3–14. In the 1970s, Gogolewski and Pennings5, 6 and Stamhuis and Pennings7 extensively investigated the structure and thermal properties of polyamide 6, polyamide 11 and polyamide 12 crystallized or annealed under high pressure and obtained the corresponding extended‐chain crystals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the thickness of the crystals was small and the growth time was long, implying that the kinetic problem resulting from the long‐chain nature of polymeric macromolecules had not been solved. Yang et al 8, 9 recently investigated the crystallization and crosslinking behaviors of polyamide 1010 with longer aliphatic segments annealed in the pressure range from 0.7 to 2.5 GPa. The results showed that the highest melting temperature and heat of fusion were 208 °C and 132.0 J g −1 respectively for a sample annealed at 1.5 GPa.…”
Section: Introductionmentioning
confidence: 99%